Mantis shrimp saddle-shaped structure biomimetic material, preparation method thereof and bone repair material
Through the preparation method of mantis shrimp saddle-shaped structure bionic material, bidirectional frozen casting, acetylation and centrifugal self-assembly technology, the problems of interface compatibility and long-term stability of organic-inorganic composite materials were solved, and high strength, high toughness and Highly biologically active bone repair material, suitable for bone defect repair.
Patent Information
- Application Number
- CN202411433551.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
AI Technical Summary
The existing organic-inorganic composite bone repair materials have shortcomings in terms of mechanical properties and biological activity, especially the problem of material interface compatibility causes mechanical properties to decline, and the long-term stability is poor, making it difficult to meet the requirements of bone defect repair.
The preparation method of mantis shrimp saddle-shaped structure bionic material is adopted, through bidirectional frozen casting, acetylation treatment and centrifugal self-assembly, combined with amorphous calcium phosphate mineralization solution, mineral content gradient distribution and structural gradient are achieved, forming high strength and high toughness and biomimicry materials with high biological activity.
Overcoming the problems of insufficient mechanical properties and biological activity of existing materials, we have prepared mantis shrimp saddle-shaped structure bionic materials with high strength, high fracture toughness and good biocompatibility, which are suitable for bone defect repair and provide new clinical practice. Application prospects.
Smart Images

Figure CN119280476A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical devices, and in particular to a mantis shrimp saddle-shaped structure bionic material and a preparation method thereof, and a bone repair material. Background Art
[0002] Organic-inorganic composite bone repair materials are a type of biomaterial used for bone tissue repair and regeneration. These materials usually combine organic polymers (such as polylactic acid, polycaprolactone, chitosan, etc.) and inorganic components (such as hydroxyapatite, calcium phosphate ceramics, silica, etc.). The organic components provide the plasticity and biodegradability of the material, while the inorganic components give the material good mechanical strength and osteoinduction properties. However, compatibility issues between different components may lead to defects at the interface of the material. For example, if the bonding strength of the phase interface is not high, it may cause stress concentration inside the material, affecting its overall mechanical properties, and even delamination, shedding or fracture during in vivo use, resulting in secondary damage; in addition, the interaction and long-term stability of organic and inorganic components in the in vivo environment are not fully understood. Undesirable interactions will not only lead to the loss of mechanical properties, but also cause changes in biological activity, thereby affecting bone repair ability. Therefore, the simple composite of several materials is difficult to meet the requirements of mechanical properties and biological activity required for bone defect repair.
[0003] The study found that the saddle-shaped tissue on the mantis shrimp's limbs is mainly composed of inorganic hydroxyapatite, amorphous calcium phosphate, calcium carbonate and organic chitin, and has excellent fracture toughness and impact resistance, which can prevent external loads from invading internal tissues and reduce the risk of failure. This unique mechanical property can be attributed to the gradient changes in the chemical composition and tissue structure of the saddle-shaped structure, that is, the outer layer has a high degree of mineralization, while the inner layer has more organic matter and a lamellar structure. This shows the application potential of mantis shrimp saddle-shaped structure bionic materials in the field of bone repair.
[0004] The existing technology only realizes the bionics of the mantis shrimp saddle-shaped chemical composition to meet the biological activity requirements, but does not realize the bionics of the mantis shrimp saddle-shaped structure. Therefore, how to prepare bionic materials with the chemical composition and structure of the mantis shrimp saddle shape to ensure its high strength and high fracture toughness mechanical properties remains to be explored. Summary of the invention
[0005] In view of this, the present invention provides a mantis shrimp saddle-shaped structure bionic material and a preparation method thereof, and a bone repair material, the main purpose of which is to prepare a mantis shrimp saddle-shaped structure bionic material with excellent strength and fracture toughness.
[0006] In order to achieve the above object, the present invention mainly provides the following technical solutions:
[0007] On the one hand, an embodiment of the present invention provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, which comprises the following steps:
[0008] The steps of preparing chitosan sponge are as follows: performing a bidirectional freeze casting process on a chitosan solution to prepare a chitosan sponge;
[0009] The step of preparing chitin sponge is: acetylation treatment is performed on the chitosan sponge to prepare chitin sponge;
[0010] The step of preparing a mineralized chitin sponge is as follows: immersing the chitin sponge in a mineralizing solution and performing a centrifugal self-assembly treatment to obtain a mineralized chitin sponge having a gradient distribution of mineral content; wherein the mineralizing solution is a mineralizing solution of amorphous calcium phosphate;
[0011] Hot pressing step: hot pressing the mineralized chitin sponge to obtain a mantis shrimp saddle-shaped structure bionic material.
[0012] Preferably, in the step of preparing chitosan sponge: injecting chitosan solution into a mold, performing bidirectional freeze casting treatment at a set temperature; demolding after the bidirectional freeze casting treatment for a set time, and then freeze drying to obtain chitosan sponge; preferably, liquid nitrogen is used as a cold source during the bidirectional freeze casting treatment; preferably, the set temperature is -60 to -100°C; preferably, the set time is 10 to 40 minutes; preferably, the freeze drying treatment time is 10 to 40 hours.
[0013] Preferably, in the step of preparing the chitosan sponge, the chitosan solution is an acetic acid solution of chitosan; wherein, in the chitosan solution, the mass fraction of chitosan is 1-5wt%, and the concentration of acetic acid is 1-10wt%; preferably, the step of preparing the chitosan solution comprises: mixing chitosan powder with deionized water, adding glacial acetic acid dropwise thereto, and then performing vacuum degassing treatment to obtain the chitosan solution; further preferably, the chitosan powder is a chitosan powder with a deacetylation degree greater than 75% and / or a chitosan powder with a deacetylation degree greater than 95%; further preferably, the rotation speed of the vacuum degassing treatment is 100-2000rpm and the time is 1-15min; preferably, the vacuum degassing treatment is performed using a vacuum mixer.
[0014] Preferably, in the step of preparing the chitin sponge: immersing the chitosan sponge in an acetylation solution for acetylation; then, removing the residual solution on the sponge after the acetylation treatment, and obtaining the chitin sponge after drying; preferably, the acetylation treatment time is 2 to 6 hours; preferably, the acetylation treatment temperature is 40 to 100°C; preferably, the acetylation treatment solution is a mixed solution of methanol and acetic anhydride; further preferably, in the acetylation treatment solution, the volume ratio of methanol to acetic anhydride is 1:1 to 20:1; further preferably, the methanol is analytically pure and the acetic anhydride is analytically pure; preferably, the acetylated sponge is ultrasonically cleaned with ethanol, ammonia water and deionized water in sequence to remove the residual solution on the sponge after the acetylation treatment.
[0015] Preferably, in the step of preparing the mineralized chitin sponge: the chitin sponge is placed in a mold containing the mineralizing solution, and subjected to centrifugal self-assembly treatment to obtain a mineralized chitin sponge with a gradient distribution of mineral content; wherein, during the centrifugal self-assembly treatment, the centrifugal rate is 10 to 200 rpm; preferably, the time of the centrifugal self-assembly treatment is 1 to 15 days, preferably 9 to 11 days; further preferably, if the time of the centrifugal self-assembly treatment is greater than 1 day, the mineralizing solution in the mold needs to be replaced every 1-2 days.
[0016] Preferably, in the step of preparing the mineralized chitin sponge: the mineralization solution is a mineralization solution of zinc-doped amorphous calcium phosphate; preferably, in the mineralization solution of zinc-doped amorphous calcium phosphate: the sum of the concentrations of calcium ions and zinc ions is 0.05-0.5 mol / L, and the molar ratio of zinc ions to calcium ions is 0.1:10-10:1; preferably, the preparation step of the zinc-doped amorphous calcium phosphate mineralization solution comprises: mixing CaCl2·2H2O, a solvent, ZnCl2, and triethylamine and reacting for a set time, then adding a phosphoric acid solution thereto, stirring for a set time, and collecting a precipitate; dispersing the precipitate in a solvent to obtain a zinc-doped amorphous calcium phosphate. Preferably, the solvent is ethanol; Preferably, CaCl2·2H2O is dissolved in ethanol, ZnCl2 is then added thereto, and triethylamine is added thereto while stirring, and after reacting for 10 to 60 minutes, an ethanol solution of phosphoric acid is added thereto, and the mixture is stirred for 12 to 36 hours; the precipitate is then collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain the zinc-doped amorphous calcium phosphate mineralization solution; Preferably, in the preparation step of the zinc-doped amorphous calcium phosphate mineralization solution, triethylamine is used as a capping agent to control the crystallization degree of the zinc-doped amorphous calcium phosphate.
[0017] Preferably, the hot pressing step comprises:
[0018] The first step is hot pressing: the mineralized chitin sponge is pressurized to 1-5 MPa at a first rate and the pressure is maintained for 1-5 hours;
[0019] The second step of hot pressing molding: after the holding time of the first step of hot pressing molding is over, the pressure is continuously increased to 50-200 MPa at a second rate, and the pressure is held for 12-24 hours to obtain a mantis shrimp saddle-shaped structure bionic material;
[0020] Preferably, the temperature of the first step of hot pressing molding is 60-100°C, and the temperature of the second step of hot pressing molding is 60-100°C;
[0021] Preferably, the first rate is 0.1-0.6 mm / min;
[0022] Preferably, the second rate is 2-10 mm / min.
[0023] Preferably, the microstructure of the chitosan sponge has a lamellar structure and the lamellae are interconnected by multiple fiber bridges; preferably, the surface of the lamellae is a smooth surface; and / or the microstructure of the chitin sponge has a lamellar structure and the lamellae are interconnected by multiple fiber bridges; preferably, the surface of the lamellae is a smooth surface; and / or the microstructure of the mineralized chitin sponge has a lamellar structure; preferably, the surface of the lamellae is a rough surface.
[0024] On the other hand, an embodiment of the present invention provides a mantis shrimp saddle-shaped structure bionic material, wherein the mineral content is distributed in a gradient that gradually decreases from the outer layer to the inner layer of the mantis shrimp saddle-shaped structure bionic material; preferably, the outer layer of the mantis shrimp saddle-shaped structure bionic material has a rough morphology, and the inner layer of the mantis shrimp saddle-shaped structure bionic material has a directional distribution of lamellar structure; preferably, in the outer layer of the mantis shrimp saddle-shaped structure bionic material, the mineral content is 50-90%; in the inner layer of the mantis shrimp saddle-shaped structure bionic material, the mineral content is 5-30%; preferably, the thickness of the mantis shrimp saddle-shaped structure bionic material is 0.1-2 mm; preferably, the flexural strength of the mantis shrimp saddle-shaped structure bionic material is 50-200 MPa, and the fracture toughness is 1-15 MPa·m 1 / 2 ; Preferably, the mantis shrimp saddle-shaped structure bionic material is prepared by any of the preparation methods described above; Preferably, the mantis shrimp saddle-shaped structure bionic material is used as or in the preparation of bone repair materials.
[0025] On the other hand, an embodiment of the present invention provides a bone repair material, wherein the bone repair material is the above-mentioned mantis shrimp saddle-shaped structure bionic material.
[0026] Compared with the prior art, the mantis shrimp saddle-shaped structure bionic material and its preparation method, and the bone repair material of the present invention have at least the following beneficial effects:
[0027] On the one hand, the embodiment of the present invention provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, first using bidirectional freezing casting to prepare chitosan sponge (lamellar structure); then acetylation of the chitosan sponge to prepare chitin sponge (lamellar structure); then, the chitin sponge is immersed in a mineralizing solution, and a slow centrifugal force self-assembly process is performed to obtain a mineralized chitin sponge with a gradient distribution of mineral content; wherein the mineralizing solution is a mineralizing solution of amorphous calcium phosphate; finally, the mineralized chitin sponge is hot-pressed to obtain a mantis shrimp saddle-shaped structure bionic material. Here, the present invention, on the basis of the above steps, selects a mineralizing solution of amorphous calcium phosphate, and cooperates with slow centrifugal force to assist self-assembly, and finally successfully prepares a bionic material with the chemical composition and structure of a bionic mantis shrimp saddle, with high strength, high toughness, and high biological activity, overcoming the barriers of insufficient mechanical properties and biological activity of existing organic-inorganic composite bone repair materials, and has important clinical application prospects.
[0028] Here, it should be noted that: in the preparation process, the present invention combines the bidirectional freezing casting technology with the slow centrifugal force assisted self-assembly, successfully prepares the mantis shrimp saddle-shaped structure bionic material, realizes the in-situ mineralization of zinc-doped amorphous calcium phosphate and chitin in the self-assembly process, eliminates the organic-inorganic phase interface, and realizes the gradient distribution of minerals. Here, zinc is an active ion for bone repair, which is used to enhance vascularization and thus accelerate the bone repair process.
[0029] Furthermore, during the preparation process, the present invention can further optimize the structure and performance of the mantis shrimp saddle-shaped structure bionic material by synergistically controlling the parameters of each step (such as the concentration of the chitosan solution, the bidirectional freezing casting temperature, the slow centrifugal force-assisted self-assembly time, the step-by-step hot pressing temperature, etc.).
[0030] On the other hand, an embodiment of the present invention provides a mantis shrimp saddle-shaped structure bionic material, which has a gradient mineral distribution, and the outer layer is a ceramic-like rough morphology, the inner layer is a horizontally distributed sheet structure, the thickness is 0.1-2 mm, the outer layer mineral content is 50-90%, and the inner layer mineral content is 5-20%; and the mantis shrimp saddle-shaped structure bionic material has a bending strength of 50-200 MPa; the fracture toughness is 1-15 MPa·m 1 / 2 .
[0031] In summary, the mantis shrimp saddle-shaped structure bionic material prepared by the present invention not only has high-strength and high-toughness mechanical properties, but also has good biocompatibility, the ability to promote angiogenesis and induce bone regeneration, providing a new strategy for bone defect repair, and can be used for bone defect repair in load-bearing or low-load-bearing areas.
[0032] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a preparation flow chart of the mantis shrimp saddle-shaped structure bionic material of the present invention;
[0034] Figure 2 This is a macroscopic physical picture of the mantis shrimp saddle-shaped structure bionic material prepared in Example 1;
[0035] Figure 3 is a microscopic morphology of the mantis shrimp saddle-shaped structure bionic material prepared in Example 1;
[0036] Figure 4 is a microscopic morphology of the mantis shrimp saddle-shaped structure bionic material prepared in Example 2;
[0037] Figure 5 is a microscopic morphology of the mantis shrimp saddle-shaped structure bionic material prepared in Example 3;
[0038] Figure 6 It is a comparative bar chart of the flexural strength of the three-point bending test and the fracture toughness of the single-edge notch tensile test of Example 1 and Example 2. DETAILED DESCRIPTION
[0039] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention application are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0040] On the one hand, the embodiment of the present invention provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, such as Figure 1 As shown, it includes the following steps:
[0041] The steps of preparing chitosan sponge are: subjecting chitosan solution to bidirectional freezing casting treatment; and freeze-drying the product of the bidirectional freezing casting treatment to obtain chitosan sponge.
[0042] More specifically, liquid nitrogen is used as a cold source, and the chitosan solution is injected into a mold, and a two-way freeze casting process is performed at a set temperature. After the freezing process is performed for 10 to 40 minutes (preferably 30 minutes), the mold is demoulded, and freeze-dried to obtain a chitosan sponge.
[0043] Preferably, the temperature of the two-way freeze casting treatment is -60 to -100°C, and the freeze drying treatment time is 10 to 40 hours. The freeze drying treatment is carried out in a freeze dryer.
[0044] In addition, about the chitosan solution used in this step, the preparation steps are as follows: chitosan powder is mixed with deionized water, and glacial acetic acid is added thereto, and vacuum degassing is carried out by a vacuum mixer to obtain a uniformly dispersed chitosan solution. Wherein, the deacetylation degree of the chitosan powder is greater than 75% and / or greater than one or more of 95%. In the chitosan solution, the mass fraction of chitosan is 1 to 5wt%, and the concentration of acetic acid is 1 to 10wt%. The chitosan solution needs to be vacuum degassed by a vacuum mixer, and the rotating speed is 100 to 2000rpm, and the processing time is 1 to 15min.
[0045] The step of preparing chitin sponge: performing acetylation treatment on the chitosan sponge to prepare the chitin sponge.
[0046] In this step, the chitosan sponge is immersed in an acetylation solution to perform acetylation treatment; then, the residual solution on the acetylated sponge is removed and dried to obtain a chitin sponge.
[0047] Preferably, the acetylation treatment time is 2 to 6 hours; the acetylation treatment temperature is 40 to 100°C; the acetylation treatment solution is a mixed solution of methanol and acetic anhydride; preferably, in the acetylation treatment solution, the volume ratio of methanol to acetic anhydride is 1:1 to 20:1.
[0048] Preferably, the acetylated sponge is ultrasonically cleaned with ethanol, ammonia water and deionized water in sequence to remove the residual solution on the acetylated sponge.
[0049] The step of preparing the mineralized chitin sponge is as follows: placing the chitin sponge in a mold containing a mineralizing solution and performing a centrifugal self-assembly process to obtain a mineralized chitin sponge with a gradient distribution of mineral content; wherein, during the centrifugal self-assembly process, the centrifugal speed is 10 to 200 rpm. The mineralizing solution is a mineralizing solution of amorphous calcium phosphate.
[0050] Preferably, the centrifugal force self-assembly treatment is performed for 1 to 15 days, preferably 9 to 11 days.
[0051] Preferably, the mineralizing solution is a zinc-doped amorphous calcium phosphate mineralizing solution.
[0052] In addition, the preparation steps of the zinc-doped amorphous calcium phosphate mineralization solution used in this step are as follows: CaCl2·2H2O is dissolved in ethanol, and then ZnCl2 is added thereto, and triethylamine is added under the condition of maintaining magnetic stirring (it should be noted that triethylamine is used as a capping agent, and the amount of triethylamine added here must satisfy that before the reaction, the molar concentration of triethylamine in the solution is A, and the sum of the molar concentrations of the calcium ions and the zinc ions is B; wherein A / B is 5 to 20;), after reacting for 1 to 60 minutes (30 minutes), an ethanol solution of phosphoric acid is added thereto, and stirred for 12 to 36 hours (preferably 24 hours); then the precipitate is collected by centrifugal enrichment and washed with ethanol (to wash away the triethylamine), and finally redispersed in ethanol to obtain the zinc-doped amorphous calcium phosphate mineralization solution. The sum of the concentrations of calcium and zinc ions in the mineralization solution is 0.05 to 0.5 mol / L, and the molar ratio of zinc ions to calcium ions is 0.1:10 to 10:1.
[0053] Preferably, triethylamine is used as a capping agent to control the crystallization degree of zinc-doped amorphous calcium phosphate;
[0054] Hot pressing step: hot pressing the mineralized chitin sponge to obtain a mantis shrimp saddle-shaped structure bionic material.
[0055] Wherein, the hot pressing forming step comprises:
[0056] The first step is hot pressing: the mineralized chitin sponge is pressurized to 1-5 MPa at a first rate and the pressure is maintained for 1-5 hours;
[0057] The second step of hot pressing molding: after the holding time of the first step of hot pressing molding is over, the pressure is continuously increased to 50-200 MPa at a second rate, and the pressure is held for 12-24 hours to obtain a mantis shrimp saddle-shaped structure bionic material;
[0058] Preferably, the temperature of the first step of hot pressing molding is 60-100°C, and the temperature of the second step of hot pressing molding is 60-100°C;
[0059] Preferably, the first rate is 0.1-0.6 mm / min;
[0060] Preferably, the second speed is 2-10 mm / min.
[0061] In addition, it should be noted that: the chitosan sponge is a yellow block structure, has a smooth layered structure at the microscopic level, and each layer is interconnected by multiple fiber bridges; the chitin sponge is a light yellow block structure and maintains the original chitosan sponge microstructure unchanged; the mineralized chitin sponge is a white block structure, the surface of the layer changes from smooth to rough, and presents a gradient distribution of zinc-doped amorphous calcium phosphate nanoparticles.
[0062] The present invention is further described below with reference to specific embodiments and comparative examples.
[0063] Example 1
[0064] This embodiment provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, comprising the following steps:
[0065] Preparation of chitosan sponge steps: weigh 2g chitosan powder and mix with 98mL deionized water, quickly add 2mL of glacial acetic acid under vigorous stirring, stir for 2min at room temperature, then place in a vacuum mixer for vacuum defoaming treatment, the treatment speed is 2000rpm, the treatment time is 1min, and a uniformly dispersed chitosan solution (acetic acid concentration is 2wt%, chitosan concentration is 2wt%) is obtained. Liquid nitrogen is used as a cold source, the chitosan solution is injected into a mold, and a two-way freeze casting process is performed at -80°C. After freezing treatment for 30 minutes, demoulding and freeze drying are performed for 10h to obtain a chitosan sponge.
[0066] Preparation of chitin sponge: Soak chitosan sponge in a mixed solution containing 100 mL of methanol and 10 mL of acetic anhydride, and place in a 45°C oven for 6 hours for acetylation. After acetylation, the sponge is ultrasonically cleaned with ethanol, ammonia water and deionized water to remove the residual solution, and then dried to obtain chitin sponge.
[0067] The steps of preparing the mineralized chitin sponge are as follows: 0.69g of CaCl2·2H2O is dissolved in 100mL of ethanol, and then 0.03g of ZnCl2 is added thereto, and 13.86mL of triethylamine is added thereto while maintaining magnetic stirring, and after reacting for 30 minutes, 260μL of phosphoric acid is added to 5mL of ethanol to form a phosphoric acid ethanol solution, and stirred for 24 hours; then the precipitate is collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain a zinc-doped amorphous calcium phosphate mineralization solution with a total concentration of calcium ions and zinc ions of 0.1mol / L; wherein the molar ratio of zinc ions to calcium ions is 0.05. The chitin sponge is placed in a mold containing 20mL of the mineralization solution, and a slow centrifugal self-assembly treatment is performed, the centrifugal rate is 80rpm, the self-assembly treatment time is 10 days, and the mineralization solution is replaced every other day to obtain a mineralized chitin sponge with a gradient distribution of mineral content.
[0068] Hot pressing molding steps: The mineralized chitin sponge is hot pressed in steps at 60°C. In the first step, the pressure is increased from no pressure to 2MPa at a rate of 0.5mm / min and maintained for 1h. In the second step, the pressure is increased to 100MPa at a rate of 2mm / min and maintained for 12h to densify the sample. After cooling, the mantis shrimp saddle-shaped structure bionic material is obtained.
[0069] The macroscopic object of the mantis shrimp saddle-shaped bionic material prepared in this embodiment is as follows: Figure 2 As shown, from Figure 2 It can be seen that the mantis shrimp saddle-shaped structure bionic material of this embodiment has a white appearance and a smooth surface.
[0070] The microscopic morphology of the mantis shrimp saddle-shaped bionic material prepared in this example is as follows: Figure 3 As shown, from Figure 3 It can be seen that the outer layer of the mantis shrimp saddle-shaped structure bionic material of this embodiment has a ceramic-like rough morphology, and the inner layer is a directional distributed lamellar structure. The overall thickness of the mantis shrimp saddle-shaped structure bionic material of this embodiment is about 1 mm.
[0071] The mantis shrimp saddle-shaped structure bionic material prepared in this embodiment was inspected and tested. The test results showed that the mineral content of the outer layer was 61.82%, and the mineral content of the inner layer was 21.4%.
[0072] Figure 6 This is a comparison chart of the bending strength of the mantis shrimp saddle-shaped bionic material prepared in this example in a three-point bending test and the fracture toughness of a single-edge notch tensile test. Figure 6 It can be seen that the bending strength of the mantis shrimp saddle-shaped bionic material of this embodiment is 160.09±5.95MPa, and the fracture toughness is 10.08±0.72MPa·m 1 / 2 .
[0073] Example 2
[0074] This embodiment provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, comprising the following steps:
[0075] Preparation of chitosan sponge steps: weigh 2g chitosan powder and mix with 98mL deionized water, quickly add 2mL of glacial acetic acid under vigorous stirring, stir for 2min at room temperature, then place in a vacuum mixer for vacuum defoaming treatment, the treatment speed is 2000rpm, the treatment time is 1min, and a uniformly dispersed chitosan solution (acetic acid concentration is 2wt%, chitosan concentration is 2wt%) is obtained. Liquid nitrogen is used as a cold source, the chitosan solution is injected into a mold, and a two-way freeze casting process is performed at -80°C. After freezing treatment for 30 minutes, demoulding and freeze drying are performed for 10h to obtain a chitosan sponge.
[0076] Preparation steps of chitin sponge: soak the chitosan sponge in a mixed solution containing 100 mL of methanol and 10 mL of acetic anhydride, and place it in a 45°C oven for 6 hours for acetylation treatment. After the acetylation treatment, the sponge is ultrasonically cleaned with ethanol, ammonia water and deionized water to remove the residual solution, and the chitin sponge is obtained after drying.
[0077] Preparation of mineralized chitin sponge: 0.69g of CaCl2·2H2O is dissolved in 100mL of ethanol, and then 0.03g of ZnCl2 is added thereto, and 13.86mL of triethylamine is added thereto while maintaining magnetic stirring. After 30 minutes of reaction, 260μL of phosphoric acid is added to 5mL of ethanol to form a phosphoric acid ethanol solution, which is stirred for 24 hours; then the precipitate is collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain a zinc-doped amorphous calcium phosphate mineralization solution with a total concentration of calcium ions and zinc ions of 0.1mol / L; wherein the molar ratio of zinc ions to calcium ions is 0.05. The chitin sponge is placed in a mold containing 20mL of mineralization solution, and slow centrifugal mineralization self-assembly is performed, the centrifugal speed is 80rpm, the self-assembly time is 5 days, and the mineralization solution is replaced every other day to obtain a mineralized chitin sponge with a gradient mineral distribution.
[0078] Hot pressing molding steps: The mineralized chitin sponge is hot pressed in steps at 60°C. In the first step, the pressure is increased from no pressure to 2MPa at a hot pressing rate of 0.5mm / min and the pressure is maintained for 1h. In the second step, the pressure is increased to 100MPa at a rate of 2mm / min and the pressure is maintained for 12h to densify the sample. After cooling, the mantis shrimp saddle-shaped structure bionic material is obtained.
[0079] Compared with Example 1, this embodiment mainly shortens the time of centrifugal force self-assembly.
[0080] The microscopic morphology of the mantis shrimp saddle-shaped bionic material prepared in this example is as follows: Figure 4 As shown, from Figure 4 It can be seen that the mantis shrimp saddle-shaped structure bionic material of this embodiment has more lamellar structures in the outer layer and lacks the rough morphology of ceramics.
[0081] Figure 6 This is a comparison chart of the bending strength of the mantis shrimp saddle-shaped bionic material prepared in this example in a three-point bending test and the fracture toughness of a single-edge notch tensile test. Figure 6 It can be seen that the bending strength of the mantis shrimp saddle-shaped bionic material of this embodiment is 81.98±12.22MPa, and the fracture toughness is 6.67±0.5MPa·m 1 / 2 .
[0082] Compared with Example 1, its bending strength and fracture toughness are lower, mainly because the mineralization self-assembly time is shortened, resulting in low mineral content and unclear gradient structure of the mantis shrimp saddle-shaped bionic material. The optimal mineralization self-assembly time is 9 to 11 days.
[0083] Example 3
[0084] This embodiment provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, comprising the following steps:
[0085] Preparation of chitosan sponge steps: weigh 4g chitosan powder and mix with 98mL deionized water, quickly add 2mL of glacial acetic acid under vigorous stirring, stir for 2min at room temperature, then place in a vacuum mixer for vacuum defoaming treatment, the treatment speed is 2000rpm, the treatment time is 1min, and a uniformly dispersed chitosan solution (acetic acid concentration is 2wt%, chitosan concentration is 4wt%) is obtained. Liquid nitrogen is used as a cold source, the chitosan solution is injected into a mold, and a two-way freeze casting process is performed while maintaining -80°C. After freezing treatment for 30 minutes, demoulding and freeze drying are performed for 10h to obtain a chitosan sponge.
[0086] The steps for preparing chitin sponge are as follows: soaking the chitosan sponge in a mixed solution containing 100 mL of methanol and 10 mL of acetic anhydride, and placing it in a 45°C oven for 6 hours for acetylation treatment; ultrasonically cleaning the acetylated sponge with ethanol, ammonia water and deionized water to remove the residual solution, and drying to obtain the chitin sponge.
[0087] Preparation of mineralized chitin sponge: 0.69g of CaCl2·2H2O is dissolved in 100mL of ethanol, and then 0.03g of ZnCl2 is added thereto, and 13.86mL of triethylamine is added thereto while maintaining magnetic stirring. After 30 minutes of reaction, 260μL of phosphoric acid is added to 5mL of ethanol to form a phosphoric acid ethanol solution, which is stirred for 24 hours; then the precipitate is collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain a zinc-doped amorphous calcium phosphate mineralization solution with a total concentration of calcium ions and zinc ions of 0.1mol / L; wherein the molar ratio of zinc ions to calcium ions is 0.05. The chitin sponge is placed in a mold containing 20mL of mineralization solution, and slow centrifugal mineralization self-assembly is performed, the centrifugal rate is 80rpm, the self-assembly time is 15 days, and the mineralization solution is replaced every other day to obtain a mineralized chitin sponge with a gradient mineral distribution.
[0088] Hot pressing molding steps: The mineralized chitin sponge is hot pressed in steps at 60°C. In the first step, the pressure is increased from no pressure to 2MPa at a hot pressing rate of 0.5mm / min and the pressure is maintained for 1h. In the second step, the pressure is increased to 100MPa at a rate of 2mm / min and the pressure is maintained for 12h to densify the sample. After cooling, the mantis shrimp saddle-shaped structure bionic material is obtained.
[0089] Compared with Example 1, this example mainly increases the concentration of chitosan and prolongs the time of centrifugal self-assembly.
[0090] The microscopic morphology of the mantis shrimp saddle-shaped bionic material prepared in this example is as follows: Figure 5 As shown, from Figure 5 It can be seen that the mantis shrimp saddle-shaped structure bionic material of this embodiment has a larger range of ceramic-like rough morphology in the outer layer, a reduced directional lamellar structure in the inner layer, and an increase in the thickness of the lamellar layer with the increase of chitosan concentration.
[0091] Example 4
[0092] This embodiment provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, comprising the following steps:
[0093] Preparation of chitosan sponge steps: weigh 2g chitosan powder and mix with 98mL deionized water, quickly add 2mL of glacial acetic acid under vigorous stirring, stir for 2min at room temperature, and then place in a vacuum mixer for vacuum defoaming treatment, the treatment speed is 500rpm, the treatment time is 1min, and a uniformly dispersed chitosan solution (acetic acid concentration is 2wt%, chitosan concentration is 2wt%) is obtained. Liquid nitrogen is used as a cold source, the chitosan solution is injected into a mold, and a two-way freeze casting treatment is performed at -80°C. After freezing treatment for 30 minutes, demoulding and freeze drying treatment are performed for 10h to obtain a chitosan sponge.
[0094] Preparation steps of chitin sponge: soak the chitosan sponge in a mixed solution containing 100 mL of methanol and 20 mL of acetic anhydride, and place it in a 45°C oven for 6 hours for acetylation treatment. After the acetylation treatment, the sponge is ultrasonically cleaned with ethanol, ammonia water and deionized water to remove the residual solution, and the chitin sponge is obtained after drying.
[0095] Preparation of mineralized chitin sponge: 0.69g of CaCl2·2H2O is dissolved in 100mL of ethanol, and then 0.03g of ZnCl2 is added thereto, and 13.86mL of triethylamine is added thereto while maintaining magnetic stirring. After reacting for 30 minutes, 260μL of phosphoric acid is added to 5mL of ethanol to form a phosphoric acid ethanol solution, which is stirred for 24 hours; then the precipitate is collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain a zinc-doped amorphous calcium phosphate mineralization solution with a total concentration of calcium ions and zinc ions of 0.1mol / L; wherein the molar ratio of zinc ions to calcium ions is 0.05. The chitin sponge is placed in a mold containing 20mL of mineralization solution, and slow centrifugal mineralization self-assembly is performed, the centrifugal rate is 80rpm, the self-assembly time is 10 days, and the mineralization solution is replaced every other day to obtain a mineralized chitin sponge with a gradient mineral distribution.
[0096] Hot pressing molding steps: The mineralized chitin sponge is hot pressed in steps at 60°C. In the first step, the pressure is increased from no pressure to 2MPa at a hot pressing rate of 0.5mm / min and the pressure is maintained for 1h. In the second step, the pressure is increased to 100MPa at a rate of 2mm / min and the pressure is maintained for 12h to densify the sample. After cooling, the mantis shrimp saddle-shaped structure bionic material is obtained.
[0097] Example 5
[0098] This embodiment provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, comprising the following steps:
[0099] Preparation of chitosan sponge steps: weigh 2g chitosan powder and mix with 98mL deionized water, quickly add 2mL of glacial acetic acid under vigorous stirring, stir for 2min at room temperature, then place in a vacuum mixer for vacuum defoaming treatment, the treatment speed is 2000rpm, the treatment time is 1min, and a uniformly dispersed chitosan solution (acetic acid concentration is 2wt%, chitosan concentration is 2wt%) is obtained. Liquid nitrogen is used as a cold source, the chitosan solution is injected into a mold, and a two-way freeze casting process is performed at -80°C. After freezing treatment for 30 minutes, demoulding and freeze drying are performed for 10h to obtain a chitosan sponge.
[0100] Preparation of chitin sponge: soaking chitosan sponge in a mixed solution containing 100 mL of methanol and 10 mL of acetic anhydride, and placing in a 55° C. oven for 4 hours for acetylation; ultrasonically cleaning the acetylated sponge with ethanol, ammonia water and deionized water to remove residual solution, and drying to obtain chitin sponge;
[0101] Preparation of mineralized chitin sponge: 1.38g of CaCl2·2H2O is dissolved in 100mL of ethanol, and then 0.06g of ZnCl2 is added thereto, and 13.86mL of triethylamine is added thereto while maintaining magnetic stirring. After reacting for 30 minutes, 260μL of phosphoric acid is added to 5mL of ethanol to form a phosphoric acid ethanol solution, which is stirred for 24 hours; then the precipitate is collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain a zinc-doped amorphous calcium phosphate mineralization solution with a total concentration of calcium ions and zinc ions of 0.2mol / L; wherein the molar ratio of zinc ions to calcium ions is 0.05. The chitin sponge is placed in a mold containing 20mL of mineralization solution, and slow centrifugal mineralization self-assembly is performed, the centrifugal rate is 80rpm, the self-assembly time is 10 days, and the mineralization solution is replaced every other day to obtain a mineralized chitin sponge with a gradient mineral distribution.
[0102] Hot pressing molding steps: The mineralized chitin sponge is hot pressed at 80°C in steps. In the first step, the pressure is increased from no pressure to 2MPa at a hot pressing rate of 0.5mm / min and the pressure is maintained for 1h. In the second step, the pressure is increased to 100MPa at a rate of 2mm / min and the pressure is maintained for 12h to densify the sample. After cooling, the mantis shrimp saddle-shaped structure bionic material is obtained.
[0103] Comparative Example 1
[0104] This comparative example provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, comprising the following steps:
[0105] Preparation of chitosan sponge steps: weigh 10g chitosan powder and mix with 97mL deionized water, quickly add 3mL of glacial acetic acid under vigorous stirring, stir for 2min at room temperature, then place in a vacuum mixer for vacuum defoaming treatment, the treatment speed is 2000rpm, the treatment time is 1min, and a uniformly dispersed chitosan solution (acetic acid concentration is 3wt%, chitosan concentration is 10wt%) is obtained. Liquid nitrogen is used as a cold source, the chitosan solution is injected into a mold, and a two-way freeze casting process is performed while maintaining -40°C. After freezing treatment for 30 minutes, demoulding and freeze drying are performed for 10h to obtain a chitosan sponge.
[0106] Preparation steps of chitin sponge: soak the chitosan sponge in a mixed solution containing 100 mL of methanol and 10 mL of acetic anhydride, and place it in a 45°C oven for 6 hours for acetylation treatment. After the acetylation treatment, the sponge is ultrasonically cleaned with ethanol, ammonia water and deionized water to remove the residual solution, and the chitin sponge is obtained after drying.
[0107] Preparation of mineralized chitin sponge: 1.38g of CaCl2·2H2O is dissolved in 100mL of ethanol, and then 0.06g of ZnCl2 is added thereto, and 13.86mL of triethylamine is added thereto while maintaining magnetic stirring. After 30 minutes of reaction, 260μL of phosphoric acid is added to 5mL of ethanol to form a phosphoric acid ethanol solution, which is stirred for 24 hours; then the precipitate is collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain a zinc-doped amorphous calcium phosphate mineralization solution with a total concentration of calcium ions and zinc ions of 0.2mol / L; wherein the molar ratio of zinc ions to calcium ions is 0.05. The chitin sponge is placed in a mold containing 20mL of mineralization solution, and slow centrifugal mineralization self-assembly is performed, the centrifugal rate is 80rpm, the self-assembly time is 12 days, and the mineralization solution is replaced every other day to obtain a mineralized chitin sponge with a gradient mineral distribution.
[0108] Hot pressing molding steps: The mineralized sponge is hot pressed at 80°C in steps. In the first step, the pressure is increased from no pressure to 2MPa at a hot pressing rate of 0.5mm / min and the pressure is maintained for 1h. In the second step, the pressure is increased to 100MPa at a rate of 2mm / min and the pressure is maintained for 12h to densify the sample. After cooling, the mantis shrimp saddle-shaped structure bionic material is obtained.
[0109] Compared with the embodiment, the sheet thickness of the mantis shrimp saddle-shaped bionic material prepared in this comparative example is increased and the directional structure is not obvious. The main reason is that the chitosan concentration is increased to 10wt%, which reduces the water content in the solution and is not conducive to the directional growth of ice crystals.
[0110] Comparative Example 2
[0111] This comparative example provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, comprising the following steps:
[0112] Preparation of chitosan sponge steps: weigh 5g chitosan powder and mix with 98mL deionized water, quickly add 2mL of glacial acetic acid under vigorous stirring, stir for 2min at room temperature, then place in a vacuum mixer for vacuum defoaming treatment, the treatment speed is 2000rpm, the treatment time is 1min, and a 5wt% chitosan solution with a uniformly dispersed 2% acetic acid concentration (acetic acid concentration is 2wt%, chitosan concentration is 5wt%) is obtained. With liquid nitrogen as a cold source, the chitosan solution is injected into a mold, and a one-way freeze casting process is carried out while maintaining at -70°C. After freezing treatment for 30 minutes, demoulding and freeze drying are carried out for 10h to obtain a chitosan sponge.
[0113] Preparation steps of chitin sponge: soak the chitosan sponge in a mixed solution containing 90 mL of methanol and 15 mL of acetic anhydride, and place it in a 45°C oven for 6 hours for acetylation treatment. After the acetylation treatment, the sponge is ultrasonically cleaned with ethanol, ammonia water and deionized water to remove the residual solution, and the chitin sponge is obtained after drying.
[0114] Preparation of mineralized chitin sponge: 1.38g of CaCl2·2H2O is dissolved in 100mL of ethanol, and then 0.06g of ZnCl2 is added, and 13.86mL of triethylamine is added under magnetic stirring. After 30 minutes of reaction, 260μL of phosphoric acid is added to 5mL of ethanol to form a phosphoric acid ethanol solution, which is stirred for 24 hours; then the precipitate is collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain a zinc-doped amorphous calcium phosphate mineralization solution with a total concentration of calcium ions and zinc ions of 0.2mol / L; wherein the molar ratio of zinc ions to calcium ions is 0.1. The chitin sponge is placed in a mold containing 20mL of the mineralization solution, and slow centrifugal mineralization self-assembly is performed, the centrifugal rate is 80rpm, the self-assembly time is 8 days, and the mineralization solution is replaced every other day to obtain a mineralized chitin sponge with a gradient mineral distribution.
[0115] Hot pressing molding steps: The mineralized sponge is hot pressed at 80°C in steps. In the first step, the pressure is increased from no pressure to 2MPa at a hot pressing rate of 0.5mm / min and the pressure is maintained for 1h. In the second step, the pressure is increased to 100MPa at a rate of 5mm / min and the pressure is maintained for 12h to densify the sample. After cooling, the mantis shrimp saddle-shaped structure bionic material is obtained.
[0116] Compared with the embodiment, the mantis shrimp saddle-shaped bionic material prepared in this comparative example does not have a directional lamellar structure. The main reason is that the unidirectional freezing casting process is used, so that the ice crystals in the chitosan solution do not grow in a directional manner along the lamellar direction.
[0117] Comparative Example 3
[0118] This comparative example provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, comprising the following steps:
[0119] Preparation of chitosan sponge steps: weigh 3g chitosan powder and mix with 98mL deionized water, quickly add 2mL of glacial acetic acid under vigorous stirring, stir for 2min at room temperature, then place in a vacuum mixer for vacuum defoaming treatment, the treatment speed is 2000rpm, the treatment time is 1min, and a uniformly dispersed chitosan solution (acetic acid concentration is 2wt%, chitosan concentration is 3wt%) is obtained. Liquid nitrogen is used as a cold source, the chitosan solution is injected into a mold, and a two-way freeze casting process is performed at -100°C, and after freezing, the mold is demoulded and freeze-dried for 10h to obtain a chitosan sponge.
[0120] Preparation steps of chitin sponge: soak the chitosan sponge in a mixed solution containing 100 mL of methanol and 10 mL of acetic anhydride, and place it in a 45°C oven for 6 hours for acetylation treatment. After the acetylation treatment, the sponge is ultrasonically cleaned with ethanol, ammonia water and deionized water to remove the residual solution and dried to obtain the chitin sponge.
[0121] Steps for preparing mineralized chitin sponge: Place the chitin sponge in a mold containing 20 mL of simulated body fluid (SBF) mineralization solution, and perform slow centrifugal mineralization self-assembly at a centrifugal rate of 80 rpm for 10 days. Replace the mineralization solution every other day to obtain a mineralized chitin sponge with a gradient mineral distribution.
[0122] Hot pressing molding steps: The mineralized chitin sponge is hot pressed at 80°C in steps. In the first step, the pressure is increased from no pressure to 2MPa at a hot pressing rate of 0.5mm / min and the pressure is maintained for 1h. In the second step, the pressure is increased to 30MPa at a rate of 3mm / min and the pressure is maintained for 12h to densify the sample. After cooling, the mantis shrimp saddle-shaped structure bionic material is obtained.
[0123] Compared with the embodiment, the mineral loading of the mantis shrimp saddle-shaped structure bionic material prepared in this comparative example is low, mainly because the zinc-doped amorphous calcium phosphate mineralization solution is replaced with SBF mineralization solution, which reduces the adsorption efficiency between the mineral and the chitin sponge.
[0124] Comparative Example 4
[0125] This comparative example provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, comprising the following steps:
[0126] Preparation of chitosan sponge steps: weigh 2g chitosan powder and mix with 99mL deionized water, quickly add 1mL of glacial acetic acid under vigorous stirring, stir for 2min at room temperature, then place in a vacuum mixer for vacuum defoaming treatment, the treatment speed is 2000rpm, the treatment time is 1min, and a uniformly dispersed chitosan solution (acetic acid concentration is 1wt%, chitosan concentration is 2wt%) is obtained. Liquid nitrogen is used as a cold source, the chitosan solution is injected into a mold, and a two-way freeze casting process is performed while maintaining -80°C. After freezing treatment for 30 minutes, demoulding and freeze drying are performed for 10h to obtain a chitosan sponge.
[0127] Preparation steps of chitin sponge: soak the chitosan sponge in a mixed solution containing 100 mL of methanol and 10 mL of acetic anhydride, and place it in a 45°C oven for 6 hours for acetylation treatment. After the acetylation treatment, the sponge is ultrasonically cleaned with ethanol, ammonia water and deionized water to remove the residual solution, and the chitin sponge is obtained after drying.
[0128] Preparation of mineralized chitin sponge: 1.38g of CaCl2·2H2O is dissolved in 100mL of ethanol, and then 0.06g of ZnCl2 is added thereto, and 13.86mL of triethylamine is added thereto while maintaining magnetic stirring. After 30 minutes of reaction, 260μL of phosphoric acid is added to 5mL of ethanol to form a phosphoric acid ethanol solution, which is stirred for 24 hours; then the precipitate is collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain a zinc-doped amorphous calcium phosphate mineralization solution with a total concentration of calcium ions and zinc ions of 0.2mol / L; wherein the molar ratio of zinc ions to calcium ions is 0.05. The chitin sponge is placed in a mold containing 20mL of mineralization solution, and slow centrifugal mineralization self-assembly is performed, the centrifugal rate is 5rpm, the self-assembly time is 10 days, and the mineralization solution is replaced every other day to obtain a mineralized chitin sponge with a gradient mineral distribution.
[0129] Hot pressing molding steps: The mineralized sponge is hot pressed at 80°C in steps. In the first step, the pressure is increased from no pressure to 2MPa at a hot pressing rate of 0.5mm / min and the pressure is maintained for 1h. In the second step, the pressure is increased to 200MPa at a rate of 2mm / min and the pressure is maintained for 12h to densify the sample. After cooling, the mantis shrimp saddle-shaped structure bionic material is obtained.
[0130] Compared with the embodiment, the minerals of the mantis shrimp saddle-shaped structure bionic material prepared in this comparative example only exist on the outer surface and do not have a gradient mineral distribution. The main reason is that the centrifugal rate of the slow centrifugal self-assembly is too low to drive the mineral gradient adsorption.
[0131] Comparative Example 5
[0132] This comparative example provides a method for preparing a mantis shrimp saddle-shaped structure bionic material, comprising the following steps:
[0133] Preparation of chitosan sponge steps: weigh 6g chitosan powder and mix with 98mL deionized water, quickly add 2mL of glacial acetic acid under vigorous stirring, stir for 2min at room temperature, then place in a vacuum mixer for vacuum defoaming treatment, the treatment speed is 2000rpm, the treatment time is 1min, and a uniformly dispersed chitosan solution (acetic acid concentration is 2wt%, chitosan concentration is 6wt%) is obtained. Liquid nitrogen is used as a cold source, the chitosan solution is injected into a mold, and a one-way freeze casting process is performed while maintaining -90°C. After freezing treatment for 30 minutes, demoulding and freeze drying are performed for 10h to obtain a chitosan sponge.
[0134] Preparation steps of chitin sponge: soak the chitosan sponge in a mixed solution containing 100 mL of methanol and 15 mL of acetic anhydride, and place it in a 45°C oven for 6 hours for acetylation treatment. After the acetylation treatment, the sponge is ultrasonically cleaned with ethanol, ammonia water and deionized water to remove the residual solution, and the chitin sponge is obtained after drying.
[0135] Preparation of mineralized chitin sponge: 0.69g of CaCl2·2H2O is dissolved in 100mL of ethanol, and then 0.03g of ZnCl2 is added thereto, and 13.86mL of triethylamine is added thereto while maintaining magnetic stirring. After 30 minutes of reaction, 260μL of phosphoric acid is added to 5mL of ethanol to form a phosphoric acid ethanol solution, which is stirred for 24 hours; then the precipitate is collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain a zinc-doped amorphous calcium phosphate mineralization solution with a total concentration of calcium ions and zinc ions of 0.1mol / L; wherein the molar ratio of zinc ions to calcium ions is 0.05. The chitin sponge is placed in a mold containing 20mL of the mineralization solution, and slow centrifugal mineralization self-assembly is performed, the centrifugal rate is 300rpm, the self-assembly time is 8 days, and the mineralization solution is replaced every other day to obtain a mineralized chitin sponge with a gradient mineral distribution.
[0136] Hot pressing molding steps: The mineralized sponge is hot pressed in steps at 60°C. In the first step, the pressure is increased from no pressure to 2MPa at a hot pressing rate of 0.2mm / min and the pressure is maintained for 1h. In the second step, the pressure is increased to 150MPa at a rate of 3mm / min and the pressure is maintained for 12h to densify the sample. After cooling, the mantis shrimp saddle-shaped structure bionic material is obtained.
[0137] Compared with the embodiment, the mantis shrimp saddle-shaped structure bionic material prepared in this comparative example has a lower mineral content and no gradient distribution. The main reason is that the centrifugal rate of centrifugal self-assembly is too fast, resulting in insufficient electrostatic adsorption reaction time between the mineral and the chitin sponge.
[0138] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a mantis shrimp saddle-shaped structure bionic material, characterized in that: It includes the following steps: The steps of preparing chitosan sponge are as follows: performing a bidirectional freeze casting process on a chitosan solution to prepare a chitosan sponge; The step of preparing chitin sponge is: acetylation treatment is performed on the chitosan sponge to prepare chitin sponge; The step of preparing a mineralized chitin sponge is as follows: immersing the chitin sponge in a mineralizing solution and performing a centrifugal self-assembly treatment to obtain a mineralized chitin sponge having a gradient distribution of mineral content; wherein the mineralizing solution is a mineralizing solution of amorphous calcium phosphate; Hot pressing step: hot pressing the mineralized chitin sponge to obtain a mantis shrimp saddle-shaped structure bionic material.
2. The method for preparing the mantis shrimp saddle-shaped structure bionic material according to claim 1, characterized in that: In the step of preparing chitosan sponge: The chitosan solution is injected into a mold and subjected to a bidirectional freezing casting treatment at a set temperature; after the bidirectional freezing casting treatment is performed for a set time, the mold is demoulded and then freeze-dried to obtain a chitosan sponge; Preferably, during the bidirectional freezing casting process, liquid nitrogen is used as a cooling source; Preferably, the set temperature is -60 to -100°C; Preferably, the set time is 10 to 40 minutes; Preferably, the freeze-drying treatment time is 10 to 40 hours.
3. The method for preparing the mantis shrimp saddle-shaped structure bionic material according to claim 1 or 2, characterized in that: In the step of preparing chitosan sponge: The chitosan solution is an acetic acid solution of chitosan; wherein, in the chitosan solution, the mass fraction of chitosan is 1-5wt%, and the concentration of acetic acid is 1-10wt%; Preferably, the preparation step of the chitosan solution comprises: mixing chitosan powder with deionized water, adding glacial acetic acid dropwise thereto, and then performing vacuum degassing treatment to obtain the chitosan solution; Further preferably, the chitosan powder is a chitosan powder with a deacetylation degree greater than 75% and / or a chitosan powder with a deacetylation degree greater than 95%; More preferably, the rotation speed of the vacuum debubbling treatment is 100 to 2000 rpm and the time is 1 to 15 min; preferably, the vacuum debubbling treatment is performed using a vacuum mixer.
4. The method for preparing the mantis shrimp saddle-shaped structure bionic material according to any one of claims 1 to 3, characterized in that: In the steps of preparing chitin sponge: Immersing the chitosan sponge in an acetylation solution to perform acetylation treatment; then removing the residual solution on the acetylated sponge and drying to obtain a chitin sponge; Preferably, the acetylation treatment time is 2 to 6 hours; Preferably, the temperature of the acetylation treatment is 40 to 100°C; Preferably, the acetylation solution is a mixed solution of methanol and acetic anhydride; further preferably, in the acetylation solution, the volume ratio of methanol to acetic anhydride is 1:1 to 20:1; further preferably, the methanol is analytically pure and the acetic anhydride is analytically pure; Preferably, the acetylated sponge is ultrasonically cleaned with ethanol, ammonia water, and deionized water in sequence to remove the residual solution on the acetylated sponge.
5. The method for preparing the mantis shrimp saddle-shaped structure bionic material according to any one of claims 1 to 4, characterized in that: In the steps of preparing mineralized chitin sponge: Placing the chitin sponge in a mold containing the mineralization solution and subjecting it to a centrifugal self-assembly treatment to obtain a mineralized chitin sponge having a gradient distribution of mineral content; wherein, during the centrifugal self-assembly treatment, the centrifugal speed is 10 to 200 rpm; Preferably, the time of the centrifugal force self-assembly treatment is 1 to 15 days, preferably 9 to 11 days; further preferably, if the time of the centrifugal force self-assembly treatment is greater than 1 day, the mineralization solution in the mold needs to be replaced every 1-2 days.
6. The method for preparing the mantis shrimp saddle-shaped structure bionic material according to any one of claims 1 to 5, characterized in that: In the steps of preparing mineralized chitin sponge: The mineralization solution is a zinc-doped amorphous calcium phosphate mineralization solution; Preferably, in the mineralization solution of the zinc-doped amorphous calcium phosphate: the sum of the molar concentrations of calcium ions and zinc ions is 0.05 to 0.5 mol / L, and the molar ratio of zinc ions to calcium ions is 0.1:10 to 10:1; Preferably, the preparation step of the zinc-doped amorphous calcium phosphate mineralization solution comprises: mixing CaCl2·2H2O, a solvent, ZnCl2, and triethylamine and reacting for a set time, then adding a phosphoric acid solution thereto, stirring for a set time, and collecting a precipitate; dispersing the precipitate in a solvent to obtain a zinc-doped amorphous calcium phosphate mineralization solution; Further preferably, the solvent is ethanol; Further preferably, CaCl2·2H2O is dissolved in ethanol, and then ZnCl2 is added thereto, and triethylamine is added thereto while maintaining stirring, and after reacting for 10 to 60 minutes, an ethanol solution of phosphoric acid is added thereto, and stirred for 12 to 36 hours; then the precipitate is collected by centrifugal enrichment and washed with ethanol, and finally redispersed in ethanol to obtain the zinc-doped amorphous calcium phosphate mineralization solution; Further preferably, in the step of preparing the zinc-doped amorphous calcium phosphate mineralization solution, triethylamine is used as a capping agent to control the degree of crystallization of the zinc-doped amorphous calcium phosphate.
7. The method for preparing the mantis shrimp saddle-shaped structure bionic material according to any one of claims 1 to 6, characterized in that: The hot pressing step comprises: The first step is hot pressing: the mineralized chitin sponge is pressurized to 1-5 MPa at a first rate and the pressure is maintained for 1-5 hours; The second step of hot pressing molding: after the holding time of the first step of hot pressing molding is over, the pressure is continuously increased to 50-200 MPa at a second rate, and the pressure is held for 12-24 hours to obtain a mantis shrimp saddle-shaped structure bionic material; Preferably, the temperature of the first step of hot pressing molding is 60-100°C, and the temperature of the second step of hot pressing molding is 60-100°C; Preferably, the first rate is 0.1-0.6 mm / min; Preferably, the second rate is 2-10 mm / min.
8. The method for preparing the mantis shrimp saddle-shaped structure bionic material according to any one of claims 1 to 7, characterized in that: The microstructure of the chitosan sponge has a lamellar structure and the lamellar layers are interconnected by a plurality of fiber bridges; preferably, the surface of the lamellar layer is a smooth surface; and / or The microstructure of the chitin sponge has a lamellar structure and the lamellar layers are interconnected by a plurality of fiber bridges; preferably, the surface of the lamellar layer is a smooth surface; and / or The microstructure of the mineralized chitin sponge has a lamellar structure; preferably, the lamellar surface is a rough surface.
9. A mantis shrimp saddle-shaped bionic material, characterized in that: From the outer layer to the inner layer of the mantis shrimp saddle-shaped structure bionic material, the mineral content is distributed in a gradient that decreases gradually; Preferably, the outer layer of the mantis shrimp saddle-shaped structure bionic material has a rough morphology, and the inner layer of the mantis shrimp saddle-shaped structure bionic material has a directional distributed lamellar structure; Preferably, in the outer layer of the mantis shrimp saddle-shaped structure bionic material, the mineral content is 50-90%; in the inner layer of the mantis shrimp saddle-shaped structure bionic material, the mineral content is 5-30%; Preferably, the thickness of the mantis shrimp saddle-shaped structure bionic material is 0.1 to 2 mm; Preferably, the mantis shrimp saddle-shaped bionic material has a bending strength of 50 to 200 MPa and a fracture toughness of 1 to 15 MPa·m 1 / 2 ; Preferably, the mantis shrimp saddle-shaped structure bionic material is prepared by the preparation method according to any one of claims 1 to 8; Preferably, the mantis shrimp saddle-shaped structure bionic material is used as or in the preparation of bone repair material.
10. A bone repair material, characterized in that: The bone repair material is the mantis shrimp saddle-shaped structure bionic material as described in claim 9.